Next generation RASR TALONTM A remote robotic rapid area sensitive site reconnaissance platform - Wells, P.; America, Q.; Lobb, T.; LaValley, H.; Rezac, J.; Chyba, T. H. (2011 IEEE International Conference on Technologies for Homeland Security, 2011)
In a joint collaboration, QinetiQ North America (QNA), Idaho National Labs (INL) and ITT are developing a ground robotic platform that provides real time remote sensitive site assessment with sensor fused area mapping, dynamic obstacle detection and avoidance, and path planning that can be retrofitted to the over 3000 fielded TALONs to date. This platform is developed under Defense Threat Reduction Agency (DTRA) Rapid Area Sensitive-Site Reconnaissance (RASR) Advanced Technical Demonstration (ATD) in conjunction with the Edgewood Chemical Biological Center. The RASR platform provides Warfighters, Civil Support Teams and First Responders with marked improvements in enhanced situational awareness and remote assessment tools.